The comfort women: A study exploring the nuances of the movement - Kalula, Musindosi (Department of Political Studies, 2024)
The term ‘comfort women' refers to victims who were abducted and forced into a system of sex trafficking that started as early as the 1930s until the end of World War II. The system was sanctioned by the Japanese government which saw its Imperial Army abducting an estimated 200,000 women and girls from nations including South Korea, China, the Philippines and Singapore. Although almost a century has passed since the system's dissolvement, it continues to be a topic of contention, particularly between South Korea and Japan, as post-colonial issues have spilled over into bilateral disagreements. Civil society organisations in South Korea have been influential in catapulting the issue onto the international stage in order for the ‘comfort women's' demands for reparations, mainly in the form of compensation and an official state apology from Japan, to be met. Additionally, organisations such as the Korean Council, have pushed for transnational women's rights to be recognised. This dissertation puts forward an important question: For a relatively successful transnational movement, how, particularly in South Korea, have demands not been met? This dissertation analyses the role a nationalist lens can create when dealing with a women's rights issue. Feminist activism grew exponentially during the 1970s and 1980s which contributed to bringing awareness to transnational women's issues such as the ‘comfort women' system. However, in the context of South Korea, there is a growing faction of nationalist activism that has placed post-colonial symbolic imagery onto the ‘comfort women' – resulting in a simplification of their trauma and demands to an ‘us' versus ‘them.'